MODIFIKASI PLATE LINER PADA AIR CHAMBER PULVERIZER DENGAN BAHAN LATE WEAR RESISTANCE ARBEX 400 - Rita Maria Veranika; Muh. Amin Fauzie; M. Iskandar Badil (Universitas Tridinanti Palembang, 2018)
Modified Plate Liners on Air Chamber Pulverizers With Wear Plate Resistance Materials Arbex 400 can extend lifetime, facilitate plate liner replacement in pulverizers (a tool for grinding and smoothing coal) due to abrasion by phyrite stones (coal follow material) which is blown by primary air scrape the liner plate cause a leak in the body air chamber pulverizer, speed up maintenance time. Modification by changing the sheet plate design into segments, adding hardness from 359 HBN (Hard Brinel Number) to 400.63 HBN and increasing plate thickness from 12 mm to 30 mm. From the evaluation after surgery for 6 months it was found that the plate liner was able to survive ± for 24 months, which previously had 8 months of abraded condition, especially the bottom to the main body.Keywords: Air Chamber, Pulverizer coal mill, Plate Liner.